Toll-Like Receptor Ligand Based Adjuvant, PorB, Increases Antigen Deposition on Germinal Center Follicular Dendritic Cells While Enhancing the Follicular Dendritic Cells Network - Lisk, Christina; Yuen, Rachel; Kuniholm, Jeff; Antos, Danielle; Reiser, Michael L.; Wetzler, Lee M. (Frontiers in Immunology, 2020)
Vaccines are arguably one of the greatest advancements in modern medicine. Subunit vaccines comprise the majority of current preparations and consist of two main components – antigen and adjuvant. The antigen is a small molecule against which the vaccine induces an immune response to provide protection via the immunostimulatory ability of the adjuvant. Our laboratory has investigated the adjuvant properties of Toll-like receptor (TLR) ligand-based adjuvants, especially the outer membrane protein from Neisseria mengingitidis, PorB. In this current study we used PorB along with CpG, an intracellular TLR-ligand based adjuvant, and a non-TLR adjuvant, aluminum salts (Alum), to further investigate cellular mechanisms of adjuvanticity, focusing on the fate of intact antigen in the germinal center and association with follicular dendritic cells (FDCs). FDCs are located in the B cell light zone of the germinal center and are imperative for affinity maturation. They are stromal cells that retain whole intact antigen allowing recognition by the B cell receptor of the germinal center B cells. Our studies demonstrate that TLR ligands, but not Alum, increase the FDC network, while PorB and Alum increased colocalization of FDC and the model soluble antigen, ovalbumin (OVA). As PorB is the only adjuvant tested that induces both a higher number of FDCs and increased deposition of antigen on FDCs, it has the greatest ability to increase FDC-antigen interaction, essential for induction of B cell affinity maturation. These studies demonstrate a further mechanism and potential superiority of PorB as an adjuvant and its influence on antibody production.